1992
DOI: 10.1007/bf00185914
|View full text |Cite
|
Sign up to set email alerts
|

The microanatomy of canine islets of Langerhans: implications for intra-islet regulation

Abstract: In recent years models for the internal ("intra-islet") regulation of hormone secretion have been proposed to explain how different islet cells might regulate each other by means of their respective secretory peptides. Models that emphasize the importance of a directed intra-islet blood flow and sequence of perfusion of islet cells rely on a certain type of islet microanatomy and vascular supply. The experimental studies underlying these models have partly been performed in dogs. To extend the incomplete morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
1
14
0
1
Order By: Relevance
“…The dog β-cells generally occupy the central portion of the islets but are also found as single cells in the exocrine pancreas (Wieczorek et al 1998), while the α-cells are generally in the periphery but also found centrally in some islets. The δ-cells are generally mixed in the islets while PP cells appear as single cells or groups (Gapp et al 1985;Redecker et al 1992). The endocrine pancreas of the Cape fur seal showed very similar morphology to what is observed in other carnivorous species like the dog and cat, and this shows a central core of β-cells surrounded by glucagon, somatostatin, and PP cells.…”
Section: Carnivorasupporting
confidence: 54%
“…The dog β-cells generally occupy the central portion of the islets but are also found as single cells in the exocrine pancreas (Wieczorek et al 1998), while the α-cells are generally in the periphery but also found centrally in some islets. The δ-cells are generally mixed in the islets while PP cells appear as single cells or groups (Gapp et al 1985;Redecker et al 1992). The endocrine pancreas of the Cape fur seal showed very similar morphology to what is observed in other carnivorous species like the dog and cat, and this shows a central core of β-cells surrounded by glucagon, somatostatin, and PP cells.…”
Section: Carnivorasupporting
confidence: 54%
“…Rabbit antibodies against fusion proteins expressed from IRSp53 or ProSAPiP1 cDNAs were as described previously Wendholt et al 2006) and were diluted between 1:500 and 1:1,000. Details of the antibodies used for the detection of pancreatic and hypophyseal hormones were as given in earlier studies (Cetin et al 1993;Redecker et al 1992Redecker et al , 1995. For the detection of growth hormone (GH) at the ultrastructural level in double-labeling experiments, a goat anti-GH antiserum (L-20) was used (Santa Cruz Biotechnology, Santa Cruz, USA).…”
Section: Antibodiesmentioning
confidence: 99%
“…8 Histology studies show similar amounts of collagen in pancreata from humans and dogs, significantly higher than those from rats. 9 Importantly, dog β cells occupy large areas of the islet core as well as the periphery, 10 similar to human but not rodent islets. 11 At the functional level, canine and human islets, in contrast to rodent islets, have similar ion-channel regulation of the electrical activity induced by glucose in β cells 12 and thus can be a helpful tool for islet research.…”
mentioning
confidence: 98%